The Influence of Initial Ability and Learning Motivation on Project Completion in Web and Mobile Programming Subjects - Himawan Sutanto; Basori Basori; Kurniasari Kurniasari (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2024)
The purpose of this study is to determine the influence of student’s initial ability and learning motivation on project completion in web and mobile programming subjects. The study was conducted using a descriptive and qualitative approach. The study subjects were class XII students of a state vocational school in Surakarta. The study was conducted in three phases: determining initial ability, determining the level of learning motivation, and analyzing the relationship between initial ability and learning motivation when completing a project. An initial ability assessment was conducted with 36 students before starting the web and mobile programming course. The determination of the level of motivation takes place after the learning process, and the final phase occurs after the learning process's completion. Data collection techniques include interviews and tests. The results of the study show that students' initial ability has a significant impact on project completion in web and mobile programming subjects.Keywords: Initial ability, Learning motivation, Subject project, Vocational school, Web and mobile programming